KESADARAN HUKUM TERHADAP PELESTARIAN PENYU DI KAMPUNG SKOUW YAMBE DISTRIK MUARA TAMI KOTA JAYAPURA PROVINSI PAPUA: LEGAL AWARENESS OF TURTLE CONSERVATION IN SKOUW YAMBE VILLAGE MUARA TAMI DISTRICT JAYAPURA CITY PAPUA PROVINCE - Mursani Mursani; Muhtar Syam; Dani Arisandi (JBMP: Jurnal Bhakti Muhammadiyah Papua, 2026)
Skouw Yambe Tourism Village or Tetang Pe is a tourism village located in Jayapura City, the capital of Papua Province. Tetang Pe is a village for 5 (five) indigenous tribes of the Skouw Yambe community. This village is directly bordered by the Pacific Ocean to the North, Holtekamp Village to the West and Skouw Mabo Village to the East and Koya Tengah Village to the South. Skouw Yambe also directly borders Papua New Guinea to the East. This village is inhabited by approximately 50 families. And is famous for its main attraction in the form of a black sand beach which is also a place where turtles come and lay their eggs, not only that, this village also has a beach tourist attraction that is approximately 5 km long and also the beauty of Tanjung Tangwato and caves that have historical value. In addition, the friendliness of the village residents makes tourists feel at home to enjoy nature until dusk welcomes, Skouw Yambe village is one of the villages that produces and supplies coconuts for Jayapura City and surrounding districts. Not only natural, cultural, and historical tourism, this village is also complemented by another unique feature, namely a turtle conservation area. The village is accessible from Jayapura city by car in about 1.5 to 2 hours, covering a distance of about 40 km. With adequate access, tourists can easily access Skouw Yambe Village.